2015
DOI: 10.1002/dev.21343
|View full text |Cite
|
Sign up to set email alerts
|

The influence of early maternal care on perceptual attentional set shifting and stress reactivity in adult rats

Abstract: Stress influences a wide variety of outcomes including cognitive processing. In the rat, early life maternal care can influence developing offspring to affect both stress reactivity and cognitive processes in adulthood. The current study assessed if variations in early life maternal care can influence cognitive performance on a task, the ability to switch cognitive sets, dependent on the medial prefrontal cortex. Early in life, offspring was reared under High or Low maternal Licking conditions. As adults, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 99 publications
(100 reference statements)
1
2
0
Order By: Relevance
“…Regarding the effect of the early environment, the present findings are consistent with previous studies, both in animal models and in humans, that have pointed to the susceptibility of cognitive flexibility to the milieu in which the individual is raised (Harms et al, 2018;Lazzaretti et al, 2018;Romero-Martínez et al, 2013;Sakhai, Saxton, & Francis, 2016;Xu et al, 2016). Our gene network was built around a select set of genes co-expressed with VAMP1, a SNARE complex protein, whose functionality in human cortex has been related to some cognitive abilities (Ramos- Miguel et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effect of the early environment, the present findings are consistent with previous studies, both in animal models and in humans, that have pointed to the susceptibility of cognitive flexibility to the milieu in which the individual is raised (Harms et al, 2018;Lazzaretti et al, 2018;Romero-Martínez et al, 2013;Sakhai, Saxton, & Francis, 2016;Xu et al, 2016). Our gene network was built around a select set of genes co-expressed with VAMP1, a SNARE complex protein, whose functionality in human cortex has been related to some cognitive abilities (Ramos- Miguel et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Mother–offspring contact has crucial effects on offspring development. Studies in rodents have shown that grooming and licking of the pups by the mother have a major impact on social and neurological development and the stress-coping abilities of the offspring [1,2,3]. In farm animal husbandry, mother–offspring contact is often greatly restricted or even absent.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive psychologists study things that people do in their heads and how they subsequently perform based on those mental operations 1 . Approximately half of all women who have an abortion have had one or more previous abortions.…”
Section: Introductionmentioning
confidence: 99%